First Pass Effect in Patients Treated With the Trevo Stent-Retriever: A TRACK Registry Study Analysis - Mokin, Maxim; Primiani, Christopher T.; Castonguay, Alicia C.; Nogueira, Raul G.; Haussen, Diogo C.; English, Joey D.; Satti, Sudhakar R.; Chen, Jennifer; Farid, Hamed; Borders, Candace; Veznedaroglu, Erol; Binning, Mandy J.; et al. (Frontiers in Neurology, 2020)
Background and Objective The first pass effect (FPE; achieving complete recanalization with a single thrombectomy device pass) has been shown to be associated with higher rates of good clinical outcomes in patients with acute ischemic stroke. Here, we investigate clinical and radiographic predictors of FPE in a large U.S. post-marketing registry (TRACK, Trevo Stent-Retriever Acute Stroke). Methods FPE was defined as a single pass/use of device, TICI 2c/3 recanalization, and no use of rescue therapy. Analysis of individual patient data from TRACK was performed to analyze clinical and radiographic predictors of FPE. Results 609 patients were included in analysis. The rate of FPE in TRACK was 23% (140/609). There was no association between patient demographics and FPE, including age (p=0.36), sex (p=0.50), race (p=0.50), location of occlusion (p=0.26), baseline NIHSS (p=0.62), or past medical history. There was no difference in the use of a balloon-guide catheter or general anesthesia (49% and 57% with FPE vs. 47% and 64%, p=0.63 and p=0.14, respectively). Clinical outcomes were significantly associated with FPE; 63% vs. 44% in non-FPE patients achieved mRS 0-2 at 90 days (p=0.0004). Conclusion Our study showed that achieving complete recanalization with a single thrombectomy pass using the Trevo device was highly beneficial. The most common clinical factors that are used to determine eligibility for endovascular therapy, such as NIHSS severity, location of occlusion or patient age were not predictive of the ability to achieve FPE.